Interpreting the Ethicality of Corporate Governance Decisions in Russia: Utilizing Integrative Social Contracts Theory to Evaluate the Relevance of Agency Theory Norms - Mccarthy, Daniel J.; Puffer, Sheila M. (Academy of Management Review, 2008)
We argue that the norms underlying agency theory can be inappropriate for interpreting the ethicality of corporate governance decisions and behaviors of Russians because they were developed in countries with mature market-oriented economies. We posit that integrative social contracts theory has more explanatory power, taking into account two sets of often-conflicting values: traditional Russian values and market-oriented values. We describe three examples of ethical conflict in Russian corporate governance arising from these two sets of values and discuss implications for Western managers interacting with Russians in this crucial area of business activity.